ANALISIS USER EXPERIENCE DAN REDESIGN USER INTERFACE WEBSITE LEMBAGA BANTUAN HUKUM JAKARTA DENGAN METODE HEURISTIC EVALUATION DAN POST STUDY SYSTEM USABILITY QUESTIONNAIRE. - Fauzan Ahmat Rahmawan (2023)
The Jakarta Legal Aid Institute (LBH) is an institution that was originally formed to provide legal assistance for people who can't afford it so they can fight for their rights. The website is one of the media used by LBH Jakarta to disseminate information regarding issues that are being guarded to make it easier for people who want to use LBH Jakarta's assistance or even want to make donations to help LBH Jakarta's struggles. Therefore, optimization of the website is important to ensure the purpose of using the website. This can be according to the needs of the community. This study aims to provide an assessment of the user experience and re-create the user interface that is able to meet the usability level of the LBH Jakarta website by using the User centered design (UCD) framework. The application of the UCD method is carried out by carrying out questionnaires and prototyping with the Heuristic evaluation technique and the Post Study System Usability Questionnaire. Through this research, researchers succeeded in increasing the user experience value based on the PSSUQ questionnaire to reach above 60% compared to the current system value. The redesign that was carried out succeeded in reducing the findings of Heuristic evaluation problems that were initially found in the running system.